Influence of the urethral pressure transducer in measuring Valsalva leak point pressure in women undergoing multichannel urodynamic testing. Issue 2 (2nd December 2019) - Panza, Joseph; Hill, Bryan; Heft, Jessica; Biller, Daniel
Abstract: Aims: To determine if the air‐charged urethral sensor balloon currently used in urodynamic testing (UDS) significantly impacts Valsalva leak point pressure (VLPP) measurements. Methods: This is a prospective cohort study of women undergoing UDS at an academic institution. VLPPs were obtained at 150 mL and urodynamic capacity with and without the urethral pressure sensor in the urethra. VLPP measurements were analyzed using a Wilcoxon signed‐rank test. Median and interquartile range are presented. Results: Sixty‐three patients were enrolled in the study, 53 were included in the primary analysis. The mean age of the subjects was 56.2 ± 12.1 years. Nine patients (16%) solely leaked when the balloon was not present in the urethra either with cough or during VLPP measurement. At both 150 mL and urodynamic capacity, when VLPP testing was performed, there was a significant difference (cmH2 O) between the control and intervention values, (76.2 [55.0, 97.0] vs 68.8 [46.3, 93.3], P = .0012; 79.3 [53, 96.5] vs 72.5 [50.8, 92.3], P = .04). There was also a statistically significant difference between the control and intervention values for the lowest leak value at 150 mL and capacity (70.5 [51, 94.5] vs 60.0 [40, 88] P = .002; 73.5 [49.5, 91.5] vs 61 [45, 88], P = .017). Conclusions: The higher VLPPs obtained with the urethral balloon in place indicate that the balloon may be the cause of falsely elevated VLPPs during urodynamic testing. Additionally, the balloon may mask a diagnosis of stress urinary incontinence in some patients.